Effect of molecular weight on the properties and organic solar cell device performance of a donor-acceptor conjugated polymer - Xiao,Z; Sun,K; Subbiah,J; Qin,T; Lu,S; Purushothaman,B; Jones,DJ; Holmes,AB; Wong,WWH (Polymer Chemistry, 2015)
Donor-acceptor conjugated polymers with 2-(2-ethylhexyl)-3-hexyl thienyl substituted benzo[1,2-b:4,5-b′]dithiophene (BDT) as donor building block and 5,6-difluorobenzo[c][1,2,5]thiadiazole as acceptor building block have been synthesized by Stille coupling polymerization. The polymerization conditions were optimized to achieve high molecular weight polymers (number-average molecular weight, Mn, up to 139 kg mol-1). The molecular weight dependent polymer properties were studied and compared. Photovoltaic applications of the polymers in bulk heterojunction (BHJ) solar cells revealed that the power conversion efficiency increased significantly (from 0.9% to 4.1%) as the Mn increased from 10 kg mol-1 to 73 kg mol-1 while further increase of the molecular weight had less influence on the solar cell performance.